Not a Hater, Just Keepin' It Real The Importance of Race- and Gender-Based Game Studies - Leonard, David J. (Games and Culture, 2006)
Notwithstanding the presence of extreme racialized tropes within the world of videogames, public discourses continue to focus on questions of violence, denying the impor-tance of games in maintaining the hegemonic racial order. Efforts to exclude race (andintersections with gender, nation, and sexuality) from public discussions through its era-sure and the acceptance of larger discourses of colorblindness contribute to a problematicunderstanding of video games and their significant role in contemporary social, political,economic, and cultural organization. How can one truly understand fantasy, violence,gender roles, plot, narrative, game playability, virtual realities, and the like without ex-amining race, racism, and/or racial stratification—one cannot. This article challengesgame studies scholars to move beyond simply studying games to begin to offer insightand analysis into the importance of race and racialized tropes within virtual reality andthe larger implications of racist pedagogies of video games in the advancement of Whitesupremacy.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Woke Gaming: Digital Challenges to Social Injustice - Gray, Kishonna L.; Leonard, David J. (University of Washington Press, 2018)
From #Gamergate to the daily experiences of marginalization among gamers, gaming is entangled with mainstream cultures of systematic exploitation and oppression. Whether visible in the persistent color line that shapes the production, dissemination, and legitimization of dominant stereotypes within the industry itself, or in the dehumanizing representations often found within game spaces, many video games perpetuate injustice and mirror the inequities and violence that permeate society as a whole. Drawing from the latest research and from popular games such as World of warcraft and Tomb raider, Woke gaming examines resistance to spaces of violence, discrimination, and microaggressions in gaming culture. The contributors of these essays identify strategies to detox gaming culture and orient players toward progressive ends, illustrating the power and potential of video games to become catalysts for social justice
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Can the Subaltern Play and Speak or Just be Played With? - Leonard, David J. (Handbook of Research on Effective Electronic Gaming in Education, 2009)
This chapter examines and responds to the silencing, resistance to any intrusion of questions about race and racism, and overall erasure of race from the debates and broader discourse concerning video game culture. It not only provides insight into the nature and logics guiding claims of colorblindness, but also connects the ideologies and culture of denial to the broader racial discourse of post-civil rights America. Hoping to inspire debate and transformative knowledge sharing, this chapter additionally offers a textually-based racial analysis of Outlaw Volleyball as an example of the type of critical examination required to move beyond a culture that often reduces bodies and voices of people of color to objects of gaze, ridicule, and consumption while denying any sorts of criticism and questions regarding the racial meaning and texts evident within much of today’s gaming.
Google-Books-ID: Re8tGpC6_PsC
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé